2014
DOI: 10.1080/13501763.2014.923022
|View full text |Cite
|
Sign up to set email alerts
|

Regional policy variation in Germany: the diversity of living conditions in a ‘unitary federal state’

Abstract: The German federal system is conventionally understood as highly coordinated between federal and regional governments and aimed at producing a 'uniformity' of living conditions. This view has increasingly been challenged as new work focuses on innovation and diversity at the regional level, and also as a consequence of reforms to the federal system that took place in 2006. This article attempts to establish a more systematic basis for assessing and explaining the scope and significance of regional policy varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(12 citation statements)
references
References 53 publications
1
10
0
1
Order By: Relevance
“…Going back to the canon of the Politikverflechtung, Jeffery et al (2014) highlight how the quintessentially entangled federal system of Germany -the template for Scharpf's joint-decision trap depiction of the EU -is nonetheless characterized by significant policy variation. Even within an integrated political system, where interdependence is strengthened via intense co-ordination legitimized by a constitutional obligation to guarantee the uniformity of living conditions, policy divergence still occurs and seems at least partially driven by institutional and party-political factors.…”
Section: The Quest For Autonomymentioning
confidence: 99%
See 2 more Smart Citations
“…Going back to the canon of the Politikverflechtung, Jeffery et al (2014) highlight how the quintessentially entangled federal system of Germany -the template for Scharpf's joint-decision trap depiction of the EU -is nonetheless characterized by significant policy variation. Even within an integrated political system, where interdependence is strengthened via intense co-ordination legitimized by a constitutional obligation to guarantee the uniformity of living conditions, policy divergence still occurs and seems at least partially driven by institutional and party-political factors.…”
Section: The Quest For Autonomymentioning
confidence: 99%
“…The first contribution by Jeffery et al (2014) picks on the case of Germany, which is an instance of a mature as well as a relatively 'unitary' federation. Indeed, owing to its highly co-ordinated nature, its dense institutional structures and constitutional requirement to provide uniform living conditions to its citizens, Germany becomes an intriguing case of the tensions between downwards dispersion, policy co-ordination and autonomy.…”
Section: Power On the Move: Upwards Sideways And Downwardsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it has also been the case in regionalized countries such as Spain and Italy, in areas such as welfare and social programme (Moreno and Trelles, 2005;Subirats, 2005;Vampa, 2014Vampa, , 2016. Even in more symmetrical systems such as Germany, where constitutional provisions theoretically guarantee a certain 'uniformity' of living conditions, significant policy divergence has been observed (Jeffery and Pamphilis, 2016;Jeffery et al, 2014). Hence, empowered regions have sought to exercise their authority in the policy sphere so that distinct preferences may translate into divergent policy outputs.…”
Section: Regions and The Policy-politics-polity Triptychmentioning
confidence: 99%
“…19 A recent analysis by Jeffery et al confirmed that the extent of policy variation between the Länder is much greater than conventionally understood. 20 In their conclusion to an edited volume examining Länder policies in 14 policy fields, Wolf and Hildebrandt also outline -beside areas of great uniformity -substantially diversified policy outputs. 21 Further analyses looking at certain policy fields produced similar results, for example, Blancke 22 (labour market policy), Münch 23 (education policy), Seeger 24 (environmental policy) and Turner 25 (education, family and childcare, labour market policy).…”
Section: A Case For Autonomous Legislation and Federal Diversitymentioning
confidence: 99%